The Influence of E-WOM on Purchasing Decisions for an Indonesian Local Cosmetic Brand on TikTok - Intan Aprilia; Haunan Damar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the era of digitalization, social media has become central to consumer interaction and purchasing behavior, with platforms like TikTok Shop enabling users to engage, share experiences, and shop seamlessly. This research examines the influence of e-WOM on purchasing decisions for Somethinc products on TikTok Shop, with brand awareness as a mediating variable. A descriptive quantitative method was employed using purposive sampling, targeting 110 Indonesian consumers who use and purchase Somethinc products on TikTok Shop. Data were collected via a questionnaire with a 1–5 Likert scale and analyzed using SmartPLS version 3, including descriptive analysis, outer and inner model evaluation, and hypothesis testing. Based on the results of the direct effect analysis, it was found that e-WOM has a positive and significant effect on Purchasing Decisions and Brand Awareness, Brand Awareness has a positive and significant effect on Purchasing Decisions. Meanwhile, the results of the indirect effect analysis indicate that e-WOM has a positive and significant effect on Purchasing Decisions through Brand Awareness. These findings suggest that Somethinc can effectively increase brand awareness and drive purchasing decisions by prioritizing high-quality e-WOM content and consistent product performance on platforms such as TikTok Shop. In addition, Gen Z consumers benefit from actively engaging with credible peer reviews and experiences to make informed and confident purchasing decisions.